DIRECTIONS FOR ENSURING THE SUSTAINABLE DEVELOPMENT OF THE INDUSTRIAL SECTOR THROUGH THE IMPLEMENTATION OF GREEN ECONOMY MECHANISMS - Yusupov Bekzod Ulugbekovich (American Journals, 2026)
The transition towards a green economy has become a strategic priority for achieving sustainable industrial development in both developed and developing countries. Industrial sectors, as major contributors to economic growth, resource consumption, and environmental degradation, require robust institutional frameworks to support green transformation. This article explores the institutional foundations necessary for ensuring sustainable development of the industrial sector through the effective implementation of green economy mechanisms. The study analyzes the role of formal and informal institutions, regulatory frameworks, economic incentives, and governance mechanisms in promoting environmentally responsible industrial growth. Using comparative analysis and a systems-based approach, the paper identifies key institutional barriers and enabling factors influencing green industrial transformation. The findings highlight that strong institutional capacity, policy coherence, stakeholder coordination, and innovation-oriented governance are critical for integrating green economy principles into industrial development strategies.
Keywords: Green economy, sustainable development, industrial sector, institutional framework, environmental governance, economic mechanisms.